IMPLIKASI GLOBALISASI TERHADAP PERKEMBANGAN DUNIA PENDIDIKAN ISLAM KONTEMPORER - Nia Wardhani (MIQOT, 2022)
Abstract: This article examines the implications of globalization on contemporary Islamic education, using a literature study. The data was obtained through literature in the form of reading books and online sources. The method used is descriptive analysis, where the method is considered appropriate to determine the ongoing phenomenon. The results of the study show that education cannot be separated from the social, economic and cultural aspects. Thinking education as something that stands alone without anything to do with the social aspects that surround it will result in real alienation. The existence of globalization has an impact on the education system and function in the form of challenges and opportunities. The challenge is how existing education can be influenced from various sectors, like the economic, social and cultural sectors. Meanwhile, opportunities can be seen how current education can create a more comprehensive and flexible education system. The world of education must organize itself to be accepted by the demands of the times, but in structuring the education system it must pay attention to the Qur'an and Sunnah as the basis for the legacy of Islamic education thought.Keywords: globalization, Islamic education, opportunities, challenges